Direct recovery of Zn from wasted alkaline batteries through selective anode's separation - V Valdrez, Inês; F Almeida, Manuel; M Dias, Joana (Journal of environmental management, 2022)
In the present study, a leaner process for recovering zinc from spent alkaline batteries is studied at a laboratory scale. Such process is part of a diagram, under development, that aims at maximizing the value of all the battery components while reducing the costs of treatment and the environmental footprint involved in recycling this waste. It starts by a physical and selective pre-treatment stage that separates the anode from the remaining components followed by neutral leaching (three washing cycles at room temperature, S/L ratio of 1/5 (w/v), magnetic stirring for 15 min and settling during 45 min), acid leaching of the washed solid (4 mol/L of sulphuric acid, S/L ratio of 1/3 (w/v), 120 min at room temperature under magnetic stirring) and, finally, electrowinning of zinc from the pregnant leach solution (100 mA/cm2, 120 min under slow magnetic stirring). By leaching the anode alone, it is possible to obtain a solution rich in zinc (86 g/L), with very low concentration of other metals (<0.08 g/L). Such solution was adequate for zinc electrowinning, allowing an average recovery rate of 58%, without applying any purification stages, at the same time regenerating sulphuric acid for its recirculation. In conclusion, the results demonstrate that a more specific physical pre-treatment stage is highly desirable to recycle spent alkaline batteries in order to reduce the number of stages involved and the overall complexity, thus, reducing the costs involved and the potential environmental impacts, while maintaining high recovery rates of zinc. [Display omitted] •A more selective dismantling of alkaline batteries is proposed for their recycling.•The technical advantages of separating the anode were assessed.•Zinc was recovered by electrowinning after neutral and acid leaching of the anode.•A recovery rate of 58% of metallic zinc was obtained.